2008
DOI: 10.1002/ffj.1866
|View full text |Cite
|
Sign up to set email alerts
|

Composition of essential oil from seeds of Nigella sativa L. cultivated in Poland

Abstract: Forty-eight compounds have been identi¼ed in the essential oil from Nigella sativa (black cumin) seeds, 14 of which are volatiles that have never been isolated from black cumin before. This is the ¼rst time to show two monoterpenoids: cis-and trans-4-methoxythujane, occur naturally in plants, speci¼cally in the essential oil from N. sativa seeds in 0.3% and 4%, respectively. The structures of the 4-methoxythujanes were established by both spectroscopic and chemical methods.SEED ESSENTIAL OIL OF NIGELLA SATIVA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
43
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 14 publications
6
43
1
Order By: Relevance
“…Traces of the esters of saturated and unsaturated fatty acids were also found in the essential oil (Burits and Bucar 2000). Two monoterpenoids including cis-and trans-4-methoxythujane were identified in the essential oil (Wajs et al 2008). Four terpenoids namely trans-(1), cis-sabinene hydrate methyl ether (2), 1,2-epoxy-menth-4-ene (3) and 1,2-epoxy-menth-4(8)-ene (4) were recently elucidated in Nigella sativa essential oil by NMR (Bourgou et al 2012).…”
Section: Medicinal Applicationsmentioning
confidence: 97%
See 1 more Smart Citation
“…Traces of the esters of saturated and unsaturated fatty acids were also found in the essential oil (Burits and Bucar 2000). Two monoterpenoids including cis-and trans-4-methoxythujane were identified in the essential oil (Wajs et al 2008). Four terpenoids namely trans-(1), cis-sabinene hydrate methyl ether (2), 1,2-epoxy-menth-4-ene (3) and 1,2-epoxy-menth-4(8)-ene (4) were recently elucidated in Nigella sativa essential oil by NMR (Bourgou et al 2012).…”
Section: Medicinal Applicationsmentioning
confidence: 97%
“…Seeds also contain 36-38 % fixed oil, alkaloids and saponins (Lautenbacher 1997;Burits and Bucar 2000;Singh et al 2005). Nigellasativa seeds contain 0.4-2.5 % essential oil and the oil used in folk medicine, as a bread or cheese flavoring and as a spice in various kinds of meals (Wajs et al 2008). To extract volatile oil, crushed seeds are extracted with organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…The proton and carbon signals due to the phenylbutenol moieties (C-1-C-4, C-1Ј-C6Ј) in the 1 H-and 13 C-NMR spectra of 1 and 2 were superimposable on those of (E)-4-(3,4-dimethoxyphenyl)but-3-en-1-ol (11), 19) whereas the signals (C-1Љ-C-10Љ) due to the monoterpene moieties were very similar to those of sabinene hydrate. 27,28) As shown in Fig. 1, the double quantum filter correlation spectroscopy (DQF COSY) experiment on 1 and 2 indicated the presence of partial structures written in bold lines, and in the heteronuclear multiple bond connectivity spectroscopy (HMBC) experiment, long-range correlations were observed between the following protons and carbons: H-1 and C-3, 1Љ; H-2 and C-4; H-3 and C-1; H-4 and C-2, 2Ј, 6Ј; H-2Ј and C-4; H-5Ј and C-3Ј; H-6Ј and C-4, 4Ј; H-2Љ and C-6Љ; H-3Љ and C-5Љ; H-5Љ and C-1Љ, 2Љ, 3Љ; H-7Љ and C-1Љ, 2Љ, 6Љ; H-8Љ and C-5Љ; 3Ј-OCH 3 and C-3Ј; 4Ј-OCH 3 and C-4Ј.…”
Section: )mentioning
confidence: 99%
“…These results are in correspondence with findings of Aitzetmüller et al [24], who identified closely related patterns of fatty acids in hexane extracts obtained from seed oils of certain species of Consolida and Delphinium genera. When comparing the analytical data from this study with previously published works on the genus Nigella, it is essential to consider differences in the extraction processes used to obtain the oils, which may significantly influence their chemical composition as previously described for N. damascena [14], N. orientalis [16], and N. sativa [8] [25]. In this view, the chemical profile of the N. hispanica oil, consisting mainly of fatty acids, greatly differs from those oils that have been previously isolated under similar extraction conditions from other species of the genus, that contain mainly mono-or sesquiterpenes [12] [13] [15] [17].…”
mentioning
confidence: 98%
“…Despite this fact, the family Ranunculaceae is still referred to, in the taxonomical literature, as a taxon not containing EOs [6]. Subsequently, works confirming EOs in seeds of N. sativa [7 -12] and other species of the Nigella genus such as N. damascena [11] [13] [14], N. orientalis [15] [16], and N. arvensis [17] have appeared in literature. In addition, the most recent articles describe occurrences of EOs in other plant parts (aerial parts, rhizomes, and flowers) of species belonging to different genera such as Aquilegia pancicii [18], Cimicifuga simplex [19], Delphinium formosum [20], Ranunculus arvensis, and R. constantinopolitanus [21].…”
mentioning
confidence: 98%